2020
DOI: 10.1136/thoraxjnl-2020-215542
|View full text |Cite
|
Sign up to set email alerts
|

Variation in oral microbiome is associated with future risk of lung cancer among never-smokers

Abstract: ObjectiveTo prospectively investigate whether diversity in oral microbiota is associated with risk of lung cancer among never-smokers.Design and settingA nested case–control study within two prospective cohort studies, the Shanghai Women’s Health Study (n=74 941) and the Shanghai Men’s Health Study (n=61 480).ParticipantsLifetime never-smokers who had no cancer at baseline. Cases were subjects who were diagnosed with incident lung cancer (n=114) and were matched 1:1 with controls on sex, age (≤2 years), date (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 22 publications
5
33
1
Order By: Relevance
“…Variations in oral microbiome have been associated with future risk of lung cancer among never-smokers. Lower microbial diversity and richness of salivary microbiota are found in non-smoking lung cancer patients and the abundance of certain specific taxa is associated with altered risk ( Yang et al, 2018 ; Hosgood et al, 2021 ). More specifically, a greater abundance of the Bacilli class and Lactobacillales order in saliva was associated with an increased risk of lung cancer, while a greater abundance of Spirochaetia and Bacteroidetes in saliva was associated with a decreased risk of lung cancer ( Hosgood et al, 2021 ).…”
Section: The Respiratory Diseases Associated With Oral Microecosystemmentioning
confidence: 99%
See 1 more Smart Citation
“…Variations in oral microbiome have been associated with future risk of lung cancer among never-smokers. Lower microbial diversity and richness of salivary microbiota are found in non-smoking lung cancer patients and the abundance of certain specific taxa is associated with altered risk ( Yang et al, 2018 ; Hosgood et al, 2021 ). More specifically, a greater abundance of the Bacilli class and Lactobacillales order in saliva was associated with an increased risk of lung cancer, while a greater abundance of Spirochaetia and Bacteroidetes in saliva was associated with a decreased risk of lung cancer ( Hosgood et al, 2021 ).…”
Section: The Respiratory Diseases Associated With Oral Microecosystemmentioning
confidence: 99%
“…Lower microbial diversity and richness of salivary microbiota are found in non-smoking lung cancer patients and the abundance of certain specific taxa is associated with altered risk ( Yang et al, 2018 ; Hosgood et al, 2021 ). More specifically, a greater abundance of the Bacilli class and Lactobacillales order in saliva was associated with an increased risk of lung cancer, while a greater abundance of Spirochaetia and Bacteroidetes in saliva was associated with a decreased risk of lung cancer ( Hosgood et al, 2021 ). Furthermore, functional analysis indicates that salivary microbiome in non-smoking female lung cancer patients is related to cancer pathways, p53 signaling pathway, apoptosis and tuberculosis ( Yang et al, 2018 ).…”
Section: The Respiratory Diseases Associated With Oral Microecosystemmentioning
confidence: 99%
“…The abundance of Veillonella , which is another dominant genus of the oral microbiota ( 56 ), was higher in the cancer group, although it did not achieve statistical significance. Overabundance of oral bacteria was found to be correlated with a spectrum of malignancies including but not limited to colorectal cancer ( 57 ), pancreatic cancer ( 58 , 59 ) and lung cancer ( 60 ). Though the relationship between oral microbiome and GC has not yet been clarified, oral microbiome has been considered as a potential biomarker for non-invasive diagnosis of GC ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…6 Multiple oral microbial taxa have been reported to be associated with increased risks of cancers. [7][8][9][10][11] In addition, a recent prospective cohort study showed that poor oral health was associated with increased gastric cancer risk. 12 To date, only four case-control studies have explored the relationship between oral microbiome and gastric cancer.…”
Section: Introductionmentioning
confidence: 99%